Base-promoted aerobic oxidation of N -alkyl iminium salts derived from isoquinolines and related heterocycles - Bai, Li-Gang; Zhou, Yue; Zhuang, Xin; Zhang, Liang; Xue, Jian; Lin, Xiao-Long; Cai, Tian; Luo, Qun-Li (Green chemistry : an international journal and green chemistry resource : GC, 2020)
Potassium tert -butoxide-promoted aerobic oxidation of N -alkyl iminium salts is reported. The reaction is atom-economical and environmentally friendly. Iminium salts derived from isoquinoline, quinoline, phenanthridine, phenanthroline, and phthalazine were successfully transformed into their corresponding unsaturated lactams with up to 95% yield under mild conditions in the absence of photocatalysts and metallic or organic catalysts. Owing to the general substrate scope, low cost, feasibility of scale up, wide availability of reagents, and green reaction conditions, this method shows great potential for preparing isoquinolones and related compounds. The method was applied for atom- and step-economical total synthesis of natural products such as norketoyobyrine.